Introduction to Digital Marketing for Youngpreneurs (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Young entrepreneurs are people who are skilled in taking advantage of opportunities in developing their business with the aim of improving life for the better, this generation is also called youngpreneurs.  Young entrepreneurs play an important role in the Indonesian economy, because their activities are considered to increase economic growth, productivity, innovation, and employment [1].     Along with the increasingly rapid changes, especially in the field of digitalization technology, these young entrepreneurs have many advantages in the use of technology that will later be useful in their business practices. Later, this generation of young entrepreneurs (youngpreneurs) is expected to increase the number of entrepreneurial needs in Indonesia to 3.95% by 2024 in accordance with the national target of the Ministry ofKopUKM [2]. The lives of these younger generations certainly cannot be separated from technology, because they were born and grew up in the midst of technological developments. The younger generation is also known as the generation that is proficient in operating the internet whether for entertainment, study, or work. Therefore, this can help the process of improving the quality of young entrepreneurs which can be done anywhere and anytime. The younger generation is guided and given knowledge about entrepreneurship not only the steps of entrepreneurship, but also to the practice of using technology, especially knowledge about digital marketing that can support entrepreneurial activities available today, such as the use of e-commerce and social media. This really needs to be done so that the younger generation accustomed to entrepreneurship can help meet the level of entrepreneurship needs. Limited resources that people have as consumers such as time and costs that cause them to prefer to shop online both using e-commerce and social media because it saves more time and costs. There are various ways to do entrepreneurship such as using existing applications, namely Instagram, TikTok, Shopee, Lazada and Tokopedia. With their expertise in social media, it will make it easier to implement a digital marketing system that in practice involves activities on social media and the internet, so that in the future it will open and expand job opportunities and help increase the number of entrepreneurial needs and achieve national entrepreneurial growth targets [3].  The partner's problem is the need for knowledge of digital marketing concepts that are relevant to the current marketing system and strategy for youngpreneurs, namely students of SMAS Methodist 1 Tanjung Morawa. The solution we offer in this service is to provide knowledge about digital marketing, especially to students who are still in high school